Dušan Lambl: the fate of scientific discoveries and the professional ethics of the great pathologist - Protsenko, Olena; Kyrychenko, Maksym; Remnyova, Natalia; Кириченко, Максим Іванович; Проценко, Олена Сергіївна; Ремньова, Наталія Олексіївна (Дніпро : Редакція журналу «Morphologia», 2020)
The great pathologist Dušan Lambl (1824–1895; Czech by origin, who lived half of his life in the Russian Empire, of which 10 years – in Kharkiv) made an invaluable contribution to the development of medical science. However, his discoveries were gradually forgotten and faded from the names of the pathogens discovered by him and the diseases they cause. In 1867, through his efforts, two new departments were established at the faculty – Histology and Pathological anatomy. The latter he headed personally until his departure to Warsaw in 1871. The surviving materials on Lambl's activities in Kharkiv are showing him as a skilful pathologist with a refined approach to his profession. Analysis of the literature on Lambl's scientific researches demonstrated a slow fading of references to his name in the titles of his discoveries. Lambl's contribution to scientific medicine is indeed great, but not appreciated deservedly. His approach to the professional activity of a pathologist and teacher can become a great example for young specialists in practical medicine, science and education.

Видатний патолог Душан Лямбль (1824-1895; чех за походженням, який прожив половину свого життя в Російській імперії, з яких 10 років – в Харкові) зробив значний внесок у розвиток медичної науки. Однак його відкриття поступово забувалися й стиралися з назв відкритих ним патогенів і хвороб, які вони викликають. Вивчення наукової спадщини Д. Лямбля і відомостей про професійну діяльність цього патолога можуть допомогти відновити знання про його науковий внесок і отримати цінні уроки для сучасних фахівців. Д. Лямбль активно розвивав в університеті викладання патологічної анатомії та гістології. У 1867 р. його зусиллями на факультеті були засновані дві нові кафедри – гістології та патологічної анатомії. Останню він очолював особисто до свого від'їзду до Варшави в 1871 р. Збережені матеріали про діяльність Д. Дямбля в Харкові розкривають його як вправного патолога з витонченим підходом до своєї професії. Аналіз літератури про наукові відкриття Д. Дямбля продемонстрував повільне загасання згадок його імені в назвах зроблених ним відкриттів. Внесок Д. Лямбля в наукову медицину дійсно значний, але не оцінений по заслугам. Його підхід до професійної діяльності патолога і викладача здатний стати прикладом для молодих фахівців практичної медицини, науки і освіти.
Keywords: Dušan Lambl; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; MEDICINE; MEDICINE::Morphology, cell biology, pathology; Сhilomastix davainei; Entamoeba histolytica